Library use and user research : with twenty case studies - Sridhar, M. S., 1949- (New Delhi : Concept Pub. Co., 2002)
With reference to users in India.
Includes bibliographical references (p. [333]-352) and index.
Keywords: Public services (Libraries) -- India -- Case studies; Library use studies -- India -- Case studies; Library science -- Data processing -- Case studies